2022
DOI: 10.3390/jcm11082240
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Mental Resilience, Mood, Coping, Personality, and Hangover Severity

Abstract: Extensive research exists on relationships between psychological constructs and alcohol consumption. However, research on relationships with hangover severity remains limited. This study aimed to assess the associations between mental resilience, mood (i.e., depression, anxiety, and stress), coping, personality, and hangover severity. A total of N = 690 participants completed an online survey by answering questions regarding their demographics, alcohol use, hangover prevalence and severity, and several psychol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 72 publications
0
12
1
Order By: Relevance
“…Previous research has been mixed regarding the link between hangover and personality, with some suggesting neuroticism predicts hangover experience [ 6 ], and others finding no association between personality and severity [ 7 ]. Our findings provide additional evidence for the link between personality and severity with results indicating that agreeableness positively predicts severity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous research has been mixed regarding the link between hangover and personality, with some suggesting neuroticism predicts hangover experience [ 6 ], and others finding no association between personality and severity [ 7 ]. Our findings provide additional evidence for the link between personality and severity with results indicating that agreeableness positively predicts severity.…”
Section: Discussionmentioning
confidence: 99%
“…One early study by Harburg et al [ 6 ] suggested that neuroticism may predict hangover, but they have since been criticized for including participants who reported no hangover symptoms. Recently, Terpstra et al [ 7 ] re-examined the link between personality and overall severity with results suggesting no association with any of the big five personality factors (Extraversion, Agreeableness, Conscientiousness, Neuroticism, Openness). These results are surprising given that individuals who score high on extraversion are more likely to binge drink [ 8 ] and greater frequency of hangovers is associated with greater subjective severity [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although hangover is 100% attributable to alcohol, certain risk factors affect hangover sensitivity and severity. Although these risk factors have received little attention in the scientific literature, several factors can aggravate the severity, including sleep deprivation, smoking, congeners, health status, genetics, sex and individual differences such as mental resilience (Jackson et al , 2013; Penning et al , 2010; Terpstra et al , 2022; Tolstrup et al , 2008). Evidence suggests that alcohol metabolites and other biological factors such as hormonal alterations and de‐regulations in cytokine pathways play a role in manifestation of hangover symptoms (Jayawardena et al , 2017).…”
Section: Purposementioning
confidence: 99%